Loss of expression of the SWI/SNF complex is a frequent event in undifferentiated/dedifferentiated urothelial carcinoma of the urinary tract - Agaimy, Abbas; Bertz, Simone; Cheng, Liang; Hes, Ondrej; Junker, Kerstin; Keck, Bastian; Lopez-Beltran, Antonio; Stoeckle, Michael; Wullich, Bernd; Hartmann, Arndt (Virchows Archiv, 2016)
Loss of the SWI/SNF chromatin remodeling complex has been recently implicated in the pathogenesis of dedifferentiated carcinomas from different organs, but its possible role in undifferentiated urothelial carcinoma (UC) has not been studied to date. In this study, we analyzed by immunohistochemistry 14 undifferentiated UCs (11 from bladder and 3 from renal pelvis) with a nondescript anaplastic or rhabdoid morphology, using commercially available antibodies against the SWI/SNF components SMARCB1 (INI1), SMARCA2, SMARCA4, SMARCC1, SMARCC2, and ARID1A. Patients were eight females and six males aged 40 to 84 years (median, 65). All tumors were muscle-invasive (9 were T3-4). A conventional UC component was seen in eight cases and varied from in situ to papillary. The undifferentiated component comprised 60-100 % of the tumors. Histologically, most tumors showed diffuse dyscohesive or pseudoalveolar growth of variably sized cells with frequent rhabdoid features. Transition from conventional to undifferentiated UC was abrupt, except in one case. The undifferentiated component almost always expressed pan-cytokeratin AE1/AE3 (13/14) and variably vimentin (8/14) and GATA3 (9/14). Complete loss of at least one SWI/SNF subunit limited to the undifferentiated component was detected in 10/14 cases (71 %). SMARCA2 was most frequently lost (six) followed by ARID1A (four), SMARCB1/INI1 (two), SMARCA4 (one), and SMARCC1 (one). This is the first study exploring SWI/SNF expression in undifferentiated UC of the urinary tract. Our results are in line with recent studies reporting involvement of the SWI/SNF complex in the dedifferentiation process of a variety of epithelial neoplasms in different organs, including the urinary tract, and association with aggressive clinical course.
EVALuna2:6799